Scooby-Doo! and the Virtual Villain : Scooby-Doo! Mysteries Series #30 - Gelsey, James; Duendes Del Sur (Firm) (New York : Scholastic, 2004)
Scooby, Shaggy, Fred, Velma, and Daphne have to delete the virtual villain before it is too late.
"A little apple paperback."
Keywords: Scooby-Doo (Fictitious character) -- Juvenile fiction; Gangs -- Fiction; Computers -- Fiction; Games -- Fiction; Mystery and detective stories